2022
DOI: 10.2147/ijn.s323802
|View full text |Cite
|
Sign up to set email alerts
|

Horseradish Peroxidase-Functionalized Gold Nanoconjugates for Breast Cancer Treatment Based on Enzyme Prodrug Therapy

Abstract: Introduction Breast cancer has the highest mortality rate among cancers in women. Patients suffering from certain breast cancers, such as triple-negative breast cancer (TNBC), lack effective treatments. This represents a clinical concern due to the associated poor prognosis and high mortality. As an approach to succeed over conventional therapy limitations, we present herein the design and evaluation of a novel nanodevice based on enzyme-functionalized gold nanoparticles to efficiently perform enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…Anti-human immunoglobulin E (IgE) is coupled to lipoic acid-modified fluorescent AuNCs to measure IgE in human serum ( Alonso et al., 2016 ). Horseradish peroxidase (HRP)-coupled AuNCs are internalized by breast cancer cells, generating free radicals and inducing apoptosis ( Vivo-Llorca et al., 2022 ).…”
Section: Justification Of Auncs For Bioimagingmentioning
confidence: 99%
“…Anti-human immunoglobulin E (IgE) is coupled to lipoic acid-modified fluorescent AuNCs to measure IgE in human serum ( Alonso et al., 2016 ). Horseradish peroxidase (HRP)-coupled AuNCs are internalized by breast cancer cells, generating free radicals and inducing apoptosis ( Vivo-Llorca et al., 2022 ).…”
Section: Justification Of Auncs For Bioimagingmentioning
confidence: 99%
“…For this reason, such enzyme-Au bioconjugates are becoming increasingly important due to their wide range of applications in the field of nanomedicine such as diagnostic and sensing methods, photothermal therapy and administration and drug delivery among others. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, such enzyme-Au bioconjugates are becoming increasingly important due to their wide range of applications in the field of nanomedicine such as diagnostic and sensing methods, photothermal therapy and administration and drug delivery among others. 19,20 In fact, only a few works have been reported in the literature on design proteins for the sustainable synthesis of Au nanoclusters. 21,22 However, in all cases, very large nanoparticle sizes are obtained, and the presence of an external reducing agent is necessary for their formation.…”
Section: Introductionmentioning
confidence: 99%
“…It can activate non-toxic indole-3-acetic acid (IAA) and other indoles into various cytotoxic free radicals such as indolyl and peroxyl radicals via single-electron oxidation under hypoxia conditions found in most tumor cells. After the initial report by Folkes et al, the effectiveness of this peroxidase-catalyzed strategy has been repeatedly demonstrated in anticancer therapy. Most reports utilize a gene-directed enzyme prodrug therapy requiring the need for delivery of the HRP gene and a successful expression in cells. ,,,, Only a few examples of the direct delivery of HRP enzymes are known. For example, chitosan nanoparticles with encapsulated HRP have been shown to activate IAA in solution, which further causes the peroxidation of membrane lipids and DNA damage that eventually triggers cellular apoptosis . Similarly, porous metal–organic frameworks were loaded with HRP to activate IAA and induce cell death …”
Section: Introductionmentioning
confidence: 99%